Dalek esa sebagai “integrating force”: Sebuah konstruksi teologis interaksi sosial masyarakat multikultural berbasis kearifan lokal di Kabupaten Rote Ndao - Pandie, Daud Alfons; Nugroho, Fibry Jati (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
There has been substantial research within Indonesian community contexts attempting to understand violent conflicts in inter-ethnic, religious, and cultural interactions. Conversely, research exploring how people can live harmoniously in social interactions across ethnic, spiritual, and cultural boundaries remains limited. This study examines the local wisdom of